Technology-Based Education Policy: Development and Implementation in the Education System - Muhammad Zein; Nurmala Sinen; Nurafni Baharuddin; Nura’na Ibrahim Sartoso (Journal of Educational Sciences, 2026)
The rapid advancement of digital technology has encouraged the implementation of technology-based education policies in Indonesia to enhance educational quality and equity. This study aims to analyze the implementation of these policies by examining infrastructure readiness, educators’ digital competence, and institutional policy support across different regional contexts. A mixed methods approach was employed, involving a survey of 600 teachers and school principals selected through stratified random sampling, complemented by interviews and focus group discussions with 25 key informants. Quantitative data were analyzed using exploratory factor analysis (EFA), structural equation modeling (SEM), and multilevel modeling, while qualitative data were analyzed thematically. The findings indicate significant disparities in technology readiness among regions. EFA identified infrastructure readiness, digital competence, and institutional support as the primary determinants of policy implementation. SEM results showed that infrastructure readiness had the strongest direct influence on implementation outcomes, while multilevel analysis revealed better performance among urban and senior high schools. Qualitative findings confirmed that limited connectivity, inadequate devices, and insufficient technical support remain major challenges, particularly in rural and 3T areas. The study concludes that successful implementation of technology-based education policies requires integrated investments in infrastructure, educator capacity development, and institutional support to promote equitable digital transformation in education.